Drought Stress Causes a Reduction in the Biosynthesis of Ascorbic Acid in Soybean Plants - Seminario, Amaia; Song, Li; Zulet, Amaia; Nguyen, Henry T.; González, Esther M.; Larrainzar, Estíbaliz (Frontiers in Plant Science, 2017)
Drought provokes a number of physiological changes in plants including oxidative damage. Ascorbic acid (AsA), also known as vitamin C, is one of the most abundant water-soluble antioxidant compound present in plant tissues. However, little is known on the regulation of AsA biosynthesis under drought stress conditions. In the current work we analyze the effects of water deficit on the biosynthesis of AsA by measuring its content, in vivo biosynthesis and the expression level of genes in the Smirnoff-Wheeler pathway in one of the major legume crop, soybean (Glycine max L. Merr). Since the pathway has not been described in legumes, we first searched for the putative orthologous genes in the soybean genome. We observed a significant genetic redundancy, with multiple genes encoding each step in the pathway. Based on RNA-seq analysis, expression of the complete pathway was detected not only in leaves but also in root tissue. Putative paralogous genes presented differential expression patterns in response to drought, suggesting the existence of functional specialization mechanisms. We found a correlation between the levels of AsA and GalLDH biosynthetic rates in leaves of drought-stressed soybean plants. However, the levels of GalLDH transcripts did not show significant differences under water deficit conditions. Among the other known regulators of the pathway, only the expression of VTC1 genes correlated with the observed decline in AsA in leaves.